KERANCUAN KALIMAT DALAM TULISAN SISWA SMA 1 SIJUNJUNG - Kartika Sari (Balai Bahasa Jawa Barat, 2017)
Writing skill involves all language skills that should be learned theoretically.It involves correct reasoning. Some people think that writing is the mostdifficult language skills. Difficulties that are often experienced by students inessay writing are how to manage a good sentence understandable by readers.Preparing a good sentence is not just constructing sentences, but to producea series of sentences that are regular and related to one another. The problemin this research is how the sentence ambiguity in students’ writings of SMA1 sijunjung. This study aims at describing the use of words in Indonesiansentences by the students of SMA 1 Sijunjung. This research uses descriptivemethod with the data sources derived from student’s writings of the school.This study found sentence ambiguity and inappropriate use of conjunctionsin their writing. The sentence ambiguity was due to the unnecessary use ofwords, the absence of the subject, and the inappropriate uses of the word. AbstrakMenulis melibatkan seluruh kemampuan berbahasa yang dipelajari secarateoretis dan melibatkan nalar yang benar. Beberapa orang beranggapan bahwamenulis termasuk keterampilan berbahasa yang paling sulit. Kesulitan yangsering dialami siswa dalam menulis karangan adalah penyusunan kalimat yangbaik agar bisa dipahami oleh pembaca. Penyusunan kalimat yang baik tidakhanya menyusun satu kalimat atau beberapa kalimat yang tidak berhubungan,tetapi menghasilkan rangkaian kalimat yang beraturan dan berhubungan satudengan yang lain. Masalah dalam penelitian ini adalah bagaimanakah kerancuankalimat dalam tulisan siswa SMA 1 Sijunjung? Penelitian ini menggunakanmetode deskriptif dengan sumber data berupa tulisan siswa SMA 1Sijunjung. Kalimat yang rancu dan ketidaktepatan penggunaan konjungtorditemukan dalam tulisan siswa SMA 1 Sijunjung. Kalimat rancu disebabkanoleh kehadiran kata yang tidak diperlukan, ketidakhadiran subjek, dan ketidaktepatanpenggunaan kata.